Antibacillus activity of diethyl ether extracts of chromolaena odorata / Rohana Mat Nor …[et al.] - Mat Nor, Rohana; Ab Rahman, Zainon; Razali, Khairul Ezwan; Mohd Noor, Zainon (2006)
Plants are rich in wide variety of compounds and many of them have been found to have antimicrobial properties. In this study, Chromolaena odorata was chosen due to its history of being used as traditional medicine to treat certain diseases. The leaf and stem samples of the plant were extracted using three different solvents: n-hexane, diethyl ether and methanol. The extraction method was carried out as in Zaidah et al. (2003). The extracts were then tested against eight ATCC target strains using standard disc diffusion assay method. Diethyl ether extracts of both leaf and stem samples showed moderate activity against Bacillus subtilis ATCC 6633 at all tested concentrations. The bioactive substances were observed to be more concentrated in the stem of the plant as the activity at the concentration of 100 µg/ml was only found from the stem extract and not from the leaf extract. All extracts were found not active against other tested microorganisms.